Validity and reliability of the measure yourself medical outcome profile 2 (MYMOP2) questionnaire among Turkish patients having anorectal disorders - Ersoy, Özdal; Temel, Yasemin Ecem; Alptekin, Hasan Kerem (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Measure Yourself Medical Outcome Profile 2 (MYMOP2) is a patient-generated outcome measure allowing patients to select the problems that are the most important to them and that they want to address, and it measures the effects of the problem from a wide range of health care interventions. This study aimed to translate the questionnaire into Turkish language (Turkish MYMOP-TMYMOP) and add this clinically useful measure to Turkish medical practice by assessing its validity and reliability. Materials and Methods: Fifty volunteers with anorectal disorders were prospectively included into the study. Each patient was enrolled into a pelvic floor training biofeedback program, specific to their anorectal symptomatology. The subjects were administered both the Nottingham Health Profile and the TMYMOP2 questionnaires before the treatment session (initial visit) and at the control follow-up visits (the first and second months, via e-mail or telephone calls). Results: The TMYMOP2 questionnaire was shown to be moderately valid (the Pearson correlation coefficient score between the total scores of the subgroups of the two questionnaires were 0.335 and 0.642, respectively, p<0.05) and highly reliable (the Cronbach’s alfa coefficient score between the total scores of the subgroups of the two questionnaires were 0.77, 0.82, and 0.88 in the beginning and at the first and second month follow-up visits, respectively). Conclusion: The TMYMOP2 was shown to be a low-to-moderately valid and a highly reliable scale. Because it is brief and short to complete, it might be an important and free-to-use tool to measure the diseases, and it can enhance the patient-centered care within the Turkish health care context. Cite this article as: Ersoy Ö, Temel YE, Alptekin HK. Validity and reliability of the measure yourself medical outcome profile 2 (MYMOP2) questionnaire among Turkish patients having anorectal disorders. Turk J Gastroenterol 2019; 30: 28-32.